PENINGKATAN HASIL BELAJAR BIOLOGI MELALUI METODE PEMBELAJARAN MIND MAPPING MATERI JARINGAN DAN ORGAN HEWAN PADA SISWA KELAS XI-IPA 1 - Imelda Santi Yuarifka (Universitas Tribhuwana Tunggadewi, 2020)
The purpose of this study was to apply the Mind mapping method to increase the creativity of students' learning outcomes in Class XI Science 1 at MAN Malang 02 Kota Batu. This type of research used is Classroom Action Research is a form of study that is descriptive in nature, to improve the rational stability and actions taken and improve the conditions under which learning practices are carried out. The research procedure was carried out in two cycles with stages of planning, implementation and reflection. The data obtained in the form of observational data and the results of the first cycle test will be compared with cycle II. The results of observations of student actions during learning increased by 20.7% of the actions of students in cycle 1 of 70.7% to 91.4%. The results of the mind mapping assessment in cycle 1 did not meet the mind mapping criteria with the acquisition of scores below the KKM and experienced an increase in cycle II, all mind mapping met the criteria with a value reaching KKM of 80. For the evaluation test results there was an increase of 76.4%, in the cycle I many students who completed KKM only 5 students with a percentage of 14.7% of 34 students who did not complete KKM with a percentage of 85.29%, while in cycle II there was an increase namely there were 31 students who completed KKM with a percentage of 91.1% and 3 students who are incomplete with a percentage of 8.82%.